Patterns of perfusion of free ALT flaps vs. propeller flaps of the lower extremity: a comparative study with the use of LDSP - Bernuth, Silvia; Niederegger, Tobias; Hundeshagen, Gabriel; Fuchs, Konrad; Meffert, Rainer H.; Jakubietz, Rafael G. (Healthcare, 2025)
Introduction: Perforator-based fasciocutaneous flaps are particularly suitable for soft tissue reconstruction of the lower extremities. The most commonly used flap is the microvascular Anterior Lateral Thigh Flap (ALT). Pedicled propeller-type flaps are less frequently utilized due to higher complication rates. The aim of this study was to compare postoperative perfusion patterns of these fundamentally different flaps to increase their basic understanding. - Methods: A retrospective data analysis was performed (2017–2022), including patients who underwent flap reconstruction of the lower extremity either with a perforator-based pedicled Propeller flap or free tissue transfer with an ALT flap. Only patients with documented postoperative perfusion monitoring of the flap using the laser Doppler spectrophotometry system (LDSP) were included. Demographic data, comorbidities and perioperative data as well as perfusion profiles given by the LDSP were analyzed. - Results: Seven patients who received a propeller flap and 18 who received a free ALT were identified. Defects were most often due to trauma (Propeller flap n = 5; 71.1%; ALT n = 7; 38.9%) and chronic wounds (Propeller flap n = 1; 14.3%; ALT n = 5; 27.8%). The most common complication was prolonged wound healing (Propeller flap n = 3; 42.9%; ALT n = 8; 44.4%). In cases with postoperative surgical complications, a distinctly delayed recovery in perfusion of propeller flaps was seen during the first 72 h after surgery. - Conclusions: Propeller and ALT flaps exhibit distinct perfusion patterns, with Propeller flaps showing a congestion-prone profile (elevated rHB, delayed hyperperfusion) and ALT flaps an inflow-dependent, ischemia-driven profile (lower rHB and SO2).
Online veröffentlicht: 26. September 2025
Gesehen am 02.02.2026